TV viewing and dreaming in children: the UK library study - Gaianigo, Julia; Schredl, Michael; Henley-Einion, Josie (International journal of dream research, 2012)
Since watching TV represents a considerable constituent of children’s waking-life, TV content should hence have a great influence on dream content. The present study in children (N = 3167) clearly indicates that most children stated that watching TV affect their dreams. Whereas the amount of TV watching is weakly associated with nightmare frequency, the children who incorporate TV contents into their dreams have more nightmares. This is most likely explained by emotional intensity experienced while watching TV and/or personality traits. Carefully designed studies eliciting TV content, emotional response to TV watching, and personality traits are necessary to better understand the effect of TV consumption on dreaming.